A structural basis for drug-induced long QT syndrome - Mitcheson, John S. (The National Academy of Sciences, 2000)
Mutations in the HERG K(+) channel gene cause inherited long QT syndrome (LQT), a disorder of cardiac repolarization that predisposes affected individuals to lethal arrhythmias [Curran, M. E., Splawski, I., Timothy, K. W., Vincent, G. M., Green, E. D. & Keating, M. T. (1995) Cell 80, 795–804]. Acquired LQT is far more common and is most often caused by block of cardiac HERG K(+) channels by commonly used medications [Roden, D. M., Lazzara, R., Rosen, M., Schwartz, P. J., Towbin, J. & Vincent, G. M. (1996) Circulation 94, 1996–2012]. It is unclear why so many structurally diverse compounds block HERG channels, but this undesirable side effect now is recognized as a major hurdle in the development of new and safe drugs. Here we use alanine-scanning mutagenesis to determine the structural basis for high-affinity drug block of HERG channels by MK-499, a methanesulfonanilide antiarrhythmic drug. The binding site, corroborated with homology modeling, is comprised of amino acids located on the S6 transmembrane domain (G648, Y652, and F656) and pore helix (T623 and V625) of the HERG channel subunit that face the cavity of the channel. Other compounds that are structurally unrelated to MK-499, but cause LQT, also were studied. The antihistamine terfenadine and a gastrointestinal prokinetic drug, cisapride, interact with Y652 and F656, but not with V625. The aromatic residues of the S6 domain that interact with these drugs (Y652 and F656) are unique to eag/erg K(+) channels. Other voltage-gated K(+) (Kv) channels have Ile and Val (Ile) in the equivalent positions. These findings suggest a possible structural explanation for how so many commonly used medications block HERG but not other Kv channels and should facilitate the rational design of drugs devoid of HERG channel binding activity.